Consumer choice of dry common beans in Malawi: The case of Lilongwe City - Tumeo, Marynia; Mapemba, Lawrence; Edriss, Abdi Khalil; Phiri, Horace (International Food Policy Research Institute, 2017)
Considering the potential of grain legumes for reducing hunger and malnutrition, this paper aims at identifying factors shaping demand for and consumption of dry common bean from a consumer’s perspective. Understanding and addressing these factors has potential to increase common bean consumption by enabling breeders to breed common beans with attributes that are preferred by consumers. The study employed a quantitative approach to assess various aspects of household common bean consumption from primary data collected in Lilongwe city. The study results suggest that socio-economic factors such as household size, education, gender, income, and number of children under the age of five years in the household play an important role in a household’s decision to consume common beans and the respective quantities consumed. Various product attributes such as grain size, gravy quality, and cooking time also influenced a household’s decision to consume common beans.